ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL−SOAL HOTS MATERI SEGIEMPAT DAN SEGITIGA DITINJAU DARI GENDER - Lulun Indraswari; Anggun Wiji Lestari; Ratri Candra Hastari (Universitas Pekalongan, 2019)
This study aims to determine the difficulties and causal factors in solving questions about the HOTS of junior high school students in terms of gender. This research is a type of descriptive research with the approach used is a qualitative approach. This research was carried out in state junior high school 1 Pogalan Trenggalek. The research subjects were 7 students in grade VII F. The instrument used is a learning implementation plan, test questions, and observation sheets. The results of the analysis indicate that the difficulties experienced by students in completing questions about HOTS indicate that male students have difficulty in the analysis and evaluation stage while female students have difficulty in the stage of evaluation and creating. As for the factors that cause difficulties experienced by students are students are not accustomed to solving questions related to the material, students are less interested in the material, an students tend to depend on the help of the teacher.